FAKTOR-FAKTOR PSIKOSOSIAL YANG MEMPENGARUHI KESEHATAN MENTAL REMAJA - Yulianti Yulianti; Novela Hayati; Lisna Wati; Muthia Fauziyyah Andini; Wafa'urrahmah Tugiartono; Dwi Indah Ramadhani (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Indonesia faces serious challenges in terms of mental health, ranking fourth in mental health disorders and fifth in anxiety worldwide, according to the 2014 WHO report. This article highlights several factors that cause mental health disorders in teenagers in Indonesia. Firstly, parenting styles play an important role, with democratic parenting that supports children's freedom, harsh authoritarian parenting, and permissive parenting that lacks care, all having different impacts on adolescent development. Conflict and negative parenting styles are associated with an increased risk of depression. Second, inadequate living environments, such as densely populated areas and damaged houses, can affect adolescents' mental health. Third, socio-economic factors such as financial stability and demands for achievement also have a significant impact on the psychological well-being of adolescents. This means that a deep understanding of these factors is very important in efforts to improve the mental health of teenagers in Indonesia.